Estudos da associação entre diabetes mellitus gestacional e periodontite: caso-controle, coorte e revisão sistemática com meta-análise - Rafael Paschoal Esteves Lima (2015)
The periodontitis in pregnant women could induce a systemic inflammatory response and lead to the development of insulin. Three studies were conducted with the aim of analyze the association between periodontitis and the gestational diabetes mellitus (DMG), the association between periodontitis and the development of type 2 diabetes mellitus (DM) in women with previous DMG and the scientific evidence on the association between periodontitis and DMG. A case-control study included 20 pregnant women with type-1 DM or type-2 DM, 20 women with DMG and 40 pregnant women without endocrine disorders were included. Gestational age, weight, height and blood glucose levels were recorded. Periodontal clinical examination was carried out. The results demonstrated that women with DMG are at high body mass index (BMI) and increased maternal age. High prevalence of periodontitis was observed, however not statistically different among the groups. A longitudinal study included 49 women with prior GDM. Blood glucose fasting, glycated hemoglobin and quantification of C-reactive protein (PCR) in the blood were requested. Clinical periodontal examination was performed during pregnancy and approximately three years after delivery. Collected stimulated whole saliva sample for quantification of interleukin-6 (IL-6), interleukin 10 (IL-10), tumor necrosis factor (TNF-), metalloproteinase 2 (MMP-2) and metalloproteinase 9 (MMP-9) was performed. The incidence of type 2 DM observed was 18.4%. There was no significant difference between groups for the frequency of periodontitis. Significant association between higher blood levels of PCR and type 2 DM was observed. Other immunological parameters did not differ between groups. In our sample no impact of periodontitis on the development of type 2 DM in women with prior DMG was observed. The association between blood PCR and the development of type 2 DM can evidence the importance of an inflammatory process in the etiology of the type 2 DM. A systematic review with meta-analysis was conducted through research in three eletronic databases. Two researches selected the studies, assessed the methodological quality, and extracted the data. One hundred ninety studies were selected. From this total, 15 studies were selected for full text analysis. Eight studies were eligible and 7 studies entered in meta-analysis. There was a significant association between periodontitis and GDM in the meta-analysis of four cross-sectional studies (OR 1.67; 95%CI 1.20-2.32). However, sensitivity test for case-control studies showed lack of consistency of data (meta-analysis of three case-control studies: OR 1.69, 95%CI 0.68-4.21). There was substantial clinical, methodological, and statistical heterogeneity among the studies. The scientific evidence cannot affirm a association between periodontitis and GDM.